Specific yield from the Mendaram peat swamp in Brunei Darussalam - Cobb, Alexander R; Harvey, Charles Franklin (In supplement to: Cobb, AR; Harvey, CF (2019): Scalar Simulation and Parameterization of Water Table Dynamics in Tropical Peatlands. Water Resources Research, 55(11), 9351-9377, https://doi.org/10.1029/2019WR025411, 2019)
The specific yield knots are recorded along with their 95% confidence intervals. Details on how they were computed from the peat surface Laplacian and throughfall and water table time series are provided inCobb and Harvey (2019).
Keywords: hydraulic conductivity; specific yield; throughfall; tropical peat swamp; water table